OUTCOME OF ZINC SUPPLEMENTATION ON NUTRITIONAL INTAKE OF CKD PATIENTS - N. Sahni; K.L. Gupta; S.V. Rana; R. Prasad; A.K. Bhalla (The Korean Society of Nephrology, 2012)
Zn, which might help in improving appetite/dietary intake by reducing taste abnormalities, is mostly available in protein rich foods. Pre-dialysis chronic kidney disease patients are advised low protein diet. This study was aimed to assess Zn status & influence of Zn supplementation on nutritional intake/appetite of 100 predialysis CKD patients not formally counseled for diet. 40 apparently healthy controls were included in the study. In group I (n=50), Zn sulphate (20mg elemental Zn) alone was given while dietary counseling [calories 35-40Kcal/kg bodyweight, proteins 0.6-0.8g/kg bodyweight (>50% high biological value)] along with Zn supplementation was given to group II (n=50). Statistical significance was calculated using SPSS Inc. version 15.0. Significantly lower nutritional & Zn status (p≤0.001) in CKD pts. as compared to controls was observed. After 1month of respective interventions, only group-II patients showed improvement in nutritional status [energy p≤0.001, protein p≤0.05, Zn (p≤0. & BMI p≤0.01, but serum Zn levels exhibited increase (p≤0.001) in group-I patients. Conclusion: Zn supplementation alone failed to improve dietary intake as it seemed patients were scared to eat more/wrong/kidney unfriendly food in absence of clear dietary guidelines, but favorable results were observed when Zn supplementation was coupled with parametric, individualized dietary counseling which shows that role of diet counseling in removing food misconceptions & lack of knowledge is important to make any therapy effective. So there is a critical need for implementation of effective nutritional management strategies.